2021
DOI: 10.1002/cnr2.1427
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of the COVID‐19 pandemic on gastrointestinal cancer care delivery

Abstract: Background and Aim This study quantifies how changes in healthcare utilization and delivery during the first months of the COVID‐19 pandemic have altered the presentation, treatment, and management of patients with gastrointestinal (GI) malignancies within an academic health system. Methods and results Patients diagnosed with a GI malignancy (ICD10: C15‐C26) who received medical care within the health system during the observation period (first 44 weeks of 2019 and 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This cohort study used patient data from a nationwide, EHR-derived deidentified clinical database to assess associations between the COVID-19 pandemic and in-person and telemedicine visit rates among patients with a broad range of indolent and aggressive hematologic neoplasms. Although several studies have evaluated changes in cancer care delivery during the pandemic, most have focused on solid organ tumors and did not evaluate visit rates in relation to therapy type . We observed a significant decline in in-person visit rates for oral therapy and outpatient infusions during the early pandemic period in all hematologic neoplasm subtypes, which later returned to forecasted rates after June 2020.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This cohort study used patient data from a nationwide, EHR-derived deidentified clinical database to assess associations between the COVID-19 pandemic and in-person and telemedicine visit rates among patients with a broad range of indolent and aggressive hematologic neoplasms. Although several studies have evaluated changes in cancer care delivery during the pandemic, most have focused on solid organ tumors and did not evaluate visit rates in relation to therapy type . We observed a significant decline in in-person visit rates for oral therapy and outpatient infusions during the early pandemic period in all hematologic neoplasm subtypes, which later returned to forecasted rates after June 2020.…”
Section: Discussionmentioning
confidence: 71%
“…Although several studies have evaluated changes in cancer care delivery during the pandemic, most have focused on solid organ tumors and did not evaluate visit rates in relation to therapy type. [8][9][10] We observed a significant decline in in-person visit rates for oral therapy and outpatient infusions during the early pandemic period in all hematologic neoplasm subtypes, which later returned to forecasted rates after June 2020. Our results mirror the findings from population-based and registry studies in other ambulatory care settings 6,22,23 and reflect disruptions from the stay-at-home orders that were in place in most of the US during that period.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Of note, most patients do not wish to change their treatment plans as recommended by guidelines developed during the pandemics[ 25 ] and this may be due to the fear and insecurity in face of the chance of having a worse prognosis because of a decrease in the frequency of care measures. Another American study that compared 25666 patients being treated for gastrointestinal cancer in 2020 and 23530 patients followed up in 2019, observed that there were statistically significant decreases in the number of radiotherapies and surgeries in patients with gastrointestinal neoplasms[ 26 ]. Sozutek et al [ 27 ] recently observed a reduction of about 70% in the volume of cases of colorectal cancer at an academic center during the pandemic.…”
Section: Treatment Of Gastrointestinal Cancer Patients During the Pan...mentioning
confidence: 99%